Odbiór reportażu literackiego w przekładzie na język macedoński - Tanuszewska, Lidia (Wydawnictwo Uniwersytetu śląskiego Katowice, 2019)
Answering the needs of the Macedonian society which is coping withe the cryses of the democracy, translators and publishers tend to reach for the literary reportage more often then before, because it reflects the contemporary world with all of its problems, known to the oppressed people. This article describes the translated books by R. Kapuściński and M. Szczygieł in the political surroundings in which they have appeared and their influence of the reception and the goal of the translation. On the other hand, the books by A. Tuszyńska and S. Alexievich are received as so-called women’s literature, considering the sensibility of the confessions of the characters.
Keywords: reception, translation, regime, women’s writing.